CHANGING THE CONTEXT OF PEDAGOGICAL INTERACTION AS A CONDITION FOR THE ORGANIZATION OF A SAFE EDUCATIONAL ENVIRONMENT UNDER THE CONDITIONS OF THE STATE OF MARTIAL - Чуйко, Олена; Гладишко, Євгенія (Видавничо-поліграфічний центр “Київський університет”, 2023)
The article updates the issue of creating a safe educational environment in the conditions of martial law, considers the main approaches that contribute to safety in education: peacebuilding and pedagogy of nonviolence, assistance for self-help as self-defense and teaching safe behavior; risk-oriented; implementation of conflict-sensitive education standards. The focus of the research is the peculiarities of pedagogical interaction between teachers and students in April–May 2022, which underwent significant changes due to the military situation in Ukraine and the forced change in the format of the educational process. The results of a survey of teaching staff of secondary education institutions (100 respondents) from 5 regions of Ukraine: Chernihiv, Kyiv, Khmelnytskyi, Ternopil and Rivne regions are given. The hypothesis about the need for teaching staff to acquire additional competencies related to providing psychosocial support to participants in the educational process, self-help and recovery methods is confirmed. It is noted that among all the components of a safe educational environment: physical (equipped and suitable bomb shelter, equipped corridors, classrooms, there is a system of warning about danger, developed rules of behavior during various types of danger, including military), social (guarantee of rights for obtaining an education at the institution, payment of wages, scholarships, compliance with the legal rights to work and rest), psychological (the feeling of security, support, comfort provided by all the staff of the institution to the participants of the educational process in view of the war situation), environmental (observance of all sanitary – hygienic rules of study and work, availability of first-aid kits in all classes, hygiene products in restrooms, access to a nurse), information (available information quality control in the educational institution, availability of anti-virus systems on computers, compliance with the rights to protect personal data, work to ensure the problems of cyberbullying and cybercrime), the most vulnerable it is physical security, and psychological safety needs improvement in its content characteristics, including by changing the content of pedagogical interaction at the "teacher-student-parent" levels.

Актуалізується питання створення безпечного освітнього середовища в сучасних умовах. Наводяться результати опитування педагогічних працівників закладів середньої освіти. Підтверджується гіпотеза про необхідність опанування педагогами компетентностей, пов'язаних із психосоціальною підтримкою учасників освітнього процесу. Зазначається, що найбільш незахищеним компонентом є фізична безпека, а психологічна безпека потребує поліпшення її змістових характеристик.
ЗМІНА КОНТЕКСТУ ПЕДАГОГІЧНОЇ ВЗАЄМОДІЇ ЯК УМОВА ОРГАНІЗАЦІЇ БЕЗПЕЧНОГО ОСВІТНЬОГО СЕРЕДОВИЩА В УМОВАХ ВОЄННОГО СТАНУ
Keywords: безпечна освіта; безпечне освітнє середовище; педагогічна взаємодія; психолого-педагогічна взаємодія; психосоціальна підтримка; safe education; safe educational environment; pedagogical interaction; psychological-pedagogical interaction; psychosocial support